ANALISIS RETORIKA JURU BICARA COVID-19 DOKTER REISA DI YOUTUBE BNPB - Rahel Putri Adhyaksa (2021)
The appearance of dr. Reisa, as the spokesperson for the handling of COVID-19, received a positive response from the public. As the main source of information and communication, spokesperson persuasion techniques are important in delivering education related to a pandemic. In this study, there is one research question, how doctor Reisa implement the five rhetorical canons. The purpose of this study was to analyze rhetorical techniques by using five rhetorical canons, namely (1) Inventio, (2) Dispositio, (3) Elocutio (4) Memoria, (5)) Pronuntitio delivered by dr. Reisa Broto Asmoro. The method used in this research is qualitative with a rhetorical analysis approach. The data technique was done by transcribing the videos held on YouTube BNPB. The data analysis techniques used were open, axial, and selective coding. Based on this study, it is concluded that, there are five rhetorical canons on press dates except for the memoria canon, then anti-intelligence rhetoric was found in this press conference.